Porphyromonas gingivalis‐nucleoside‐diphosphate‐kinase inhibits ATP‐induced reactive‐oxygen‐species via P2X7 receptor/NADPH‐oxidase signalling and contributes to persistence. (9th January 2013) - Choi, Chul Hee; Spooner, Ralee; DeGuzman, Jefferson; Koutouzis, Theofilos; Ojcius, David M.; Yilmaz, Özlem
Summary Ligation of P2X7 receptors with a 'danger signal', extracellular ATP (eATP), has recently been shown to result in production of intracellular reactive‐oxygen‐species (ROS) in macrophages. We show that primary gingival epithelial cells (GECs) produce sustained, robust cellular ROS upon stimulation by eATP. The induction of ROS was mediated by P2X7 receptor signalling coupled with NADPH‐oxidase activation, as determined by pharmacological inhibition and RNA interference. Furthermore, Porphyromonas gingivalis, an oral opportunistic pathogen, upregulated the antioxidant glutathione response, modulated eATP‐induced cytosolic and mitochondrial ROS generated through P2X7/NADPH‐oxidase interactome, and subsequently blocked oxidative stress in GECs via temporal secretion of a P. gingivalis effector, nucleoside‐diphosphate‐kinase (Ndk). An ndk‐deficient P. gingivalis mutant lacked the ability to inhibit ROS production and persist intracellularly following eATP stimulation. Treatment with recombinant Ndk significantly diminished eATP‐evoked ROS production. P. gingivalis infection elicited a strong, time‐dependent increase in anti‐oxidativemitochondrial UCP2 levels, whereas ndk‐deficient mutant did not cause any change. The results reveal a novel signalling cascade that is tightly coupled with eATP signalling and ROS regulation. Ndk by P. gingivalis counteracts these antimicrobial signalling activities by secreting Ndk, thus contributing to successful persistence of the pathogen.